Scistocormus fissispinalis monster in a buffalo - CHANDOLIA, R K; CHANDER, S; KUMAR, ASHOK; SINGH, PREM (The Indian Journal of Animal Reproduction, 2023)
A case of scistocormus fissispinalis a rare case of its kind has been reported in buffalo.
Keywords: Monster; Scistocormus fissispanils; buffalo